ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT DI KELAS VII C SMP NEGERI 6 PALU: Analysis of Student Errors in Solving Addition and Subtraction of Integers in Class VII Cof SMP Negeri 6 Palu - Putri Rezkia; Baharuddin Paloloang; Ibnu Hadjar (Jurnal Elektronik Pendidikan Matematika Tadulako, 2025)
This study aims to obtain a description of the types of student errors in solving addition and subtraction of integers in class VII C of SMP Negeri 6 Palu. This type of research is descriptive research using a qualitative approach. The subjects of this study were three students of class VII C who had high, medium and low levels of mathematical ability. The results of this study indicate that subjects with high mathematical abilities make conceptual errors with an error indicator, namely not knowing the formula used. Subjects with mathematical abilities are making conceptual errors with an error indicator, namely not knowing the formula used. Technical errors with error indicators, namely making mistakes in arithmetic operations. Subjects with low mathematical abilities made conceptual errors with error indicators, namely not being able to apply the formula. Technical errors with error indicators, namely making mistakes in arithmetic operation, then the subject made a mistake in moving the numbers or arithmetic operations from one step to the next.